Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.7897/2230-8407.0508133
|View full text |Cite
|
Sign up to set email alerts
|

Collection, Detection, Assessment, Monitoring and Prevention of Adverse Drug Reactions of Anti-Epileptic Drugs

Abstract: An adverse drug reaction (ADR) as defined by World Health Organization (WHO) is a noxious, unintended effect of a drug, occurring at normal doses in humans for prophylaxis, diagnosis or therapy of disease or for the modification of physiological function. ADRs rank among the top ten leading causes of mortality. The adverse effects (AEs) of antiepileptic drugs (AEDs) are highly prevalent and can be potentially life threatening. The objective of this study is to identify the ADR by chart review method, to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…This finding is supported by study conducted by Prudhivi et al, in which out of 130 ADR cases reported, type A cases were 66.15%. 8 On age distribution maximum ADRs were found in age group 71-80 years age group, as there is lower renal and hepatic microsomal drug metabolizing activity, elderly are more prone to develop cumulative toxicity while receiving prolonged medication. This distribution is in contrast to a study conducted by Thaha et al in which majority of patients were in age group 50-59 years.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is supported by study conducted by Prudhivi et al, in which out of 130 ADR cases reported, type A cases were 66.15%. 8 On age distribution maximum ADRs were found in age group 71-80 years age group, as there is lower renal and hepatic microsomal drug metabolizing activity, elderly are more prone to develop cumulative toxicity while receiving prolonged medication. This distribution is in contrast to a study conducted by Thaha et al in which majority of patients were in age group 50-59 years.…”
Section: Discussionmentioning
confidence: 96%